The Role of Demand and Investment in Long-Term Growth - Cornwall, John (Quarterly Journal of Economics, 1970)
I. Introduction, 48. — II. Two alternative interpretations of the stylized facts, 49. — III. The influence of supply on demand, 53. — IV. The influence of demand on supply, 56. — V. Growth and transformation, 60. —VI. Say's law in reverse, 65. — VII. Summary, 68.